Transition us together: development of a parent-centered toolkit to support adolescents with rheumatic disease transition to adult care - Dushnicky Molly J.; Scott Jessica; McCauley Dayle; Gorter Jan Willem; Beattie Karen A.; Batthish Michelle (De Gruyter, 2022)
While the transition period can be a difficult time for adolescents with chronic health conditions, parents also face challenges in understanding their changing role and how to support their children. To date, minimal interventions have focused on supporting and empowering parents during this period.